Inefectividad de los líderes para dirigir equipos jóvenes (2022)
The research work carried out is aimed at knowing the appropriate leadership styles to seek that workers of young generations such as Millennials and Centennials have an outstanding performance within organizations and are oriented to the generation of value for stakeholders, for which carried out a non-experimental quantitative study with cross-sectional data collection and the focus group technique was used to approach the subject. The objective of this work is to identify the leadership styles that should be used by people who are located in the chain of command within organizations and that will be more effective when directing the new workforce. This objective will be carried out through a survey and interviews to identify which factors are key when a Millennial or a Centennial finds themselves within an organization and they feel motivated, feel committed and are more productive within the organization. the same.